Bifidobacterium animalis suppresses non-small cell lung cancer progression and modulates tumor immunity through indole-3-acetic acid - Qian Song; Xinpei Li; Qing Li; Shijie Shang; Shuling Ma; Zijun Zhai; Fengxin Sun; You Mo; Ling Wei; Meng Wu; Yuequn Ma; Jinming Yu; et al. (Cell Reports)
Summary: Emerging evidence implicates the significant influence of gut microbiome and its metabolic byproducts in the non-small cell lung cancer (NSCLC). Here, we identify distinct disparity in the gut microbiota composition between patients with NSCLC and healthy controls, with Bifidobacterium animalis being markedly decreased in NSCLC. B. animalis suppresses tumor progression in two NSCLC mouse models and NSCLC cell lines. Integrative metabolomic analysis identifies indole-3 acetic acid (IAA) as the pivotal metabolite of B. animalis, with significant anti-NSCLC properties. Mechanistically, B. animalis and its derived IAA activate aryl hydrocarbon receptor (AHR) in lung to suppress METTL3 and the m6A methylation of STAT3. Moreover, B. animalis and IAA diminish polarization of M2 macrophage and enhance CD8+ T cell functions by suppressing interleukin-6 (IL-6). B. animalis and its derived IAA protect against NSCLC by modulating AHR/METTL3/STAT3 and bolstering antitumor immunity through gut-lung axis. B. animalis and IAA supplementation represent a promising prophylactic for NSCLC prevention.